Agatha raisin and the murderous marriage eaudiobook - Beaton, M. C. (Agatha Raisin Mystery, 2012)
Almost bigamy and absolute murder—Agatha Raisin's life is never dull. The morning of Agatha's longed-for marriage to James Lacey dawns bright and clear. But her luck runs out in the church when Jimmy, the husband she had believed long dead, turns up large as life and twice as ugly. Agatha has a go at strangling him. It's all too much for James, who breaks off the engagement. So when Jimmy is found murdered the next day, Agatha and James are both suspects. And they'll have to work together in order to clear their names.